Determination of band offset in MgO/InP heterostructure by X-ray photoelectron spectroscopy. (December 2016) - Liu, Xue; Wang, Xiaohua; Wang, Dengkui; Tang, Jilong; Fang, Xuan; Fang, Dan; Li, Yongfeng; Yao, Bin; Ma, Xiaohui; Wang, Haizhu; Wei, Zhipeng
Abstract: X-ray photoelectron spectroscopy was used to measure the valence-band offset ( ΔE V ) of MgO/InP heterostructure. Two sets of core level pairs in the MgO/InP system were used to demonstrate the accuracy of the calculation, the ΔE V value was the same (5.33 ± 0.15 eV) when using the In 3d3/2, Mg 2p pair and In 3d5/2, Mg 2p pair, indicating our calculations are accuracy and reasonable. Taking the band gaps of 7.83 eV for MgO and 1.34 eV for InP into consideration, a type-I band alignment of MgO/InP heterostructure was obtained with conduction band offset (CBO) of 1.16 ± 0.15 eV for two sets of core level pairs, indicating a nested interface band alignment heterostructure was prepared. The accurate determination of the band alignment of MgO/InP has a significant impact on the performance of InP-based devices. Highlights: Valence band offset of MgO/InP heterojunction was measured by X-ray photoelectron spectroscopy. Two sets of core level pairs in the MgO/InP system were used to demonstrate the accuracy of the calculation. The valence-band and conduction-band offset were 5.33 eV and 1.16 eV for two sets of core level pairs. Formation of considerable space charge like layer at the interface of MgO/InP heterostructure.